Self-Censorship Among Student Journalists Based on Perceived Threats and Risks. (September 2019) - Farquhar, Lee K.; Carey, Michael Clay
This research analyzes news-making decisions and self-censorship among student journalists through the lens of gatekeeping theory. Using Q methodology, the study examines responses of 45 student journalists who were asked about variables that would influence their decisions not to pursue a controversial story. Four factors emerged based on analysis of three principal variables: the source of perceived threats, the nature of those threats, and the parties most likely to suffer if the threats come to fruition.